Molecular classification of rumen fluke eggs in fecal specimens from Suphanburi Province, Thailand, based on cytochrome C oxidase subunit 1 - Sothorn Anucherngchai (2020)
© 2020 Elsevier B.V. Rumen fluke infections have been known to cause paramphistomiasis in both wild and domestic animals worldwide. Occasionally, coinfections of rumen flukes (Carmyerius, Fischoederius, and Paramphistomum) with liver flukes (Fasciola) have been observed due to the similar life cycles that these two species share. This study involved an alternative approach that was developed to classify and distinguish rumen fluke eggs from other genera by using the polymerase chain reaction (PCR) method based on cytochrome c oxidase subunit 1 (COI). Thirty-eight fecal specimens of Bos taurus from Suphanburi Province, Central Thailand were examined using the formalin–ether sedimentation technique. PCR detection was then performed using COI-specific primers that were developed in this study. The results showed that this primer set can classify and distinguish the egg specimens into a separate clade of the genera comprising Gastrothylax, Carmyerius, Fischoederius, Paramphistomum, Explanatum, and Fasciola. Moreover, epidemiological mapping revealed coinfections of three genera of rumen flukes at some collection sites, leading to the need to further investigate Paramphistomoidea infection along with Fasciolidae infection within the endemic area. This data is important for monitoring the outbreak of these parasites in Suphanburi Province, Thailand. It can be applied for initiating surveillance programs of paramphistomiasis and fascioliasis in veterinary studies.